Increased risk of ovarian and breast malignancies in women with polycystic ovary syndrome: a review article: Risk of ovarian and breast malignancies with PCOS - Chen, Huiqing; Jiang, Qian; Yin, Yanru (Cellular and Molecular Biology, 2023)
Polycystic ovary syndrome (PCOS) is one of the common abnormalities in 5 to 8% of reproductive-age women, which is associated with high levels of androgens and polycystic ovaries. A clear connection between the level of sex hormones and some women's cancers and infertility abnormalities has been identified. Investigating common mutations in ovarian and breast cancer in people with PCOS can help to better understand the risk and their relationship. Epidemiological data suggest that the induction and biology of breast and ovarian cancer are related to estrogen levels. According to molecular findings, there are common mutations in BRCA genes in ovarian and breast cancer and PCOS patients. The BRCA1 gene produces proteins that prevent malignant tumor formation in the body. Despite common cancer mutations, there is a risk of ovarian and breast cancer in polycystic patients, and these mutations can confirm the risk of ovarian and breast cancer in PCOS patients. Of course, long-term laboratory studies are needed to confirm this relationship. In addition, the presence of genetic mutations can be considered a predisposing marker in connection with ovarian and breast cancer onset, and this awareness can be effective in preventing them from developing in the future.